Effects of Whole-body Vibration Training on Sprint Running Kinematics and Explosive Strength Performance - Giorgos, Paradisis (Asist Group, 2007)
The aim of this study was to investigate the effect of 6 wk of whole body vibration (WBV) training on sprint running kinematics and explosive strength performance. Twenty-four volunteers (12 women and 12 men) participated in the study and were randomised (n = 12) into the experimental and control groups. The WBV group performed a 6-wk program (16-30 min·d(-1), 3 times a week) on a vibration platform. The amplitude of the vibration platform was 2.5 mm and the acceleration was 2.28 g. The control group did not participate in any training. Tests were performed Pre and post the training period. Sprint running performance was measured during a 60 m sprint where running time, running speed, step length and step rate were calculated. Explosive strength performance was measured during a counter movement jump (CMJ) test, where jump height and total number of jumps performed in a period of 30 s (30CVJT). Performance in 10 m, 20 m, 40 m, 50 m and 60 m improved significantly after 6 wk of WBV training with an overall improvement of 2.7%. The step length and running speed improved by 5.1% and 3.6%, and the step rate decreased by 3.4%. The countermovement jump height increased by 3.3%, and the explosive strength endurance improved overall by 7.8%. The WBV training period of 6 wk produced significant changes in sprint running kinematics and explosive strength performance.